Evaluasi Kelayakan Finansial Usaha Peternakan Ayam Broiler di CV Cendana Farm Indonesia - Irfan Maulana Ahsan; Hayatul Millah; Cici Widya Prasetyandari (Jurnal Ekonomi Syariah Pelita Bangsa, 2025)
This study aims to evaluate the broiler poultry business at CV Cendana Farm Indonesia, Dandang unit, which has a chicken population of 24,000. The study will discuss the comparison between revenue, production costs, and profits from the broiler poultry business, as well as assess its financial feasibility through calculations of NPV, IRR, PI, PP. The research method used is a descriptive quantitative approach, with primary data obtained through interviews with staff and directors, while secondary data is taken from financial reports over 12 harvest periods. The financial feasibility evaluation is conducted using calculations of NPV, IRR, PI and PP. The results show that the business is not feasible in the short term (NPV -445,634,638, IRR -8%), but feasible if operated for 5 years (NPV 992,170,708, IRR 46.8%). A PI greater than 1 (1.32) and a PP of 1 year 8 months indicate long-term profitability.